Nepali Sahitya Samalochanama Riti Siddhanta - Bhatta, Ram Chandra (Tribhuvan University Journal, 2011)
Not Available. Key words: Nepali Literature; Riti; Samalochana Tribhuvan University Journal Vol XXIII, No. 1, 2001 Page: 129-137 Uploaded date: 21 April, 2011